Antimicrobial performance of Ti-doped ZnO thin films with a fixed Ti:Zn molar ratio - Aksan, Onur Alp; Berikten, Derya; Oral, Ahmet Yavuz; Bahsi, Zehra Banu (Wiley, 2025)
Ti-doped ZnO films were synthesized via the sol-gel dip-coating method with a fixed Ti:Zn molar ratio of 0.2:1 to investigate their structural, optical, and antimicrobial properties. X-ray diffraction analysis confirmed the hexagonal wurtzite ZnO structure with a (002) preferred orientation, while scanning electron microscopy (SEM) and atomic force microscopy revealed compact nanostructures with uniform grain distribution. Raman spectroscopy displayed the characteristic E-2(high) mode associated with crystal quality, along with red shifts in the A(1)(longitudinal optical) and 2LA modes, indicating lattice deformation induced by Ti incorporation. The prism coupler yielded a film thickness of approximately 1 mu m and a refractive index of 1.96. The porosity was estimated as 13.4% using optical data and 14.8% via SEM-based ImageJ analysis. Ultraviolet-visible (UV-Vis) spectroscopy revealed high transparency in the visible range (>95%) and strong UV absorption, with a reduced optical band gap of 3.17 eV, suggesting bandgap narrowing due to defect formation and lattice strain. Antimicrobial activity tests showed a reduction of up to 99.96% of Acinetobacter baumannii and remarkable activity against other strains, including Candida parapsilosis (96.8%) and Enterococcus faecalis (83%) after UV light exposure. Although Staphylococcus aureus showed lower sensitivity (similar to 43%), the overall results indicate that Ti-doped ZnO films are promising candidates for multifunctional applications requiring high optical quality and effective antimicrobial surface activity.
Keywords: antimicrobial activity; optical properties; sol-gel dip-coating; Ti-doped ZnO thin films